Prevalence and factors associated with depressive symptoms among Polish dentistry students - Drożak, Paulina; Drożak, Martyna; Augustowska, Katarzyna; Bryliński, Łukasz; Bura, Agata; Duda, Piotr (Journal of Education, Health and Sport, 2020)
Introduction and objective. Depression is a disease that affects over 264 million people worldwide. According to research, the problem of depression concerns dentistry students. The aim of the research was to investigate the prevalence and severity of depressive symptoms among Polish dental students, determine factors associated with this phenomenon and examine the relationship between these factors and depressive symptoms. Material and method. The participants of the study were dental students enrolled in each of the 10 Polish universities that offer dental education. The research tool was an author’s questionnaire and a Polish-language version of 9-Item-Patient Health Questionnaire (PHQ-9). Results. A total of 247 dental students took part in the study. The statistical analysis showed that 53.85% of the respondents were provisionally diagnosed with major depression. 8.91% of the participants had symptoms of severe depression. The research suggests that not doing sports regularly and not getting enough sleep are factors associated with depression among Polish dental students. Conclusions. Depressive symptoms among Polish dental students are common. Results suggest that it is important for students to maintain physical activity and take care of proper sleep hygiene. Further research needs to be done in order to explore more factors associated with depressive symptoms in the above-mentioned group.